Fundamental solutions of thermoelasticity with a recent heat conduction model with a single delay term - Kumari B.; Mukhopadhyay S. (My University, 2025)
The present work is concerned with the thermoelasticity theory based on a very recently proposed heat conduction model—a heat conduction model with a delay term introduced by Quintanilla. Here we aim to obtain the fundamental solutions of thermoelasticity in the context of this theory. We derive the solution of Galerkin-type field equations for the case of homogeneous and isotropic bodies. With the help of this solution, we determine the effects of concentrated heat sources and body forces in an unbounded medium. We further obtain the fundamental solutions of the field equations in case of steady vibrations. © 2017 Taylor & Francis.